Implikasi Technological Pedagogical Content Knowledge (TPACK) dengan Information Comunication and Technology (ICT) pada Pembelajaran PAI di SMAN 1 Beber - Saehu Abas; Yandi Wahyu Hidayat; Rozha Fadhlu Rohman (Indonesian Journal of Islamic Education Studies (INJURIES), 2023)
The main problem in this study is the low learning outcomes of students of Class XI SMA Negeri 1 Beber Cirebon. One of the factors causing low student learning outcomes is the conventional approach to learning, so as to make students passive in learning that affects their learning outcomes. The purpose of the study to be achieved is to determine the improvement of learning outcomes through tpack approach in Grade 11 students of SMA Negeri 1 Beber Cirebon. The research method used is class action research, this study was conducted in 2 cycles with a total of 35 students. Each cycle consists of planning, carrying out actions, observation and reflection. Data collection techniques using test, data analysis techniques used using descriptive quantitative. The results showed student learning outcomes in cycle I with a percentage of learning completion of 77% or 27 students who achieve the minimum completion criteria of 35 students, while Cycle 2 with a percentage of learning completion of 97% or 34 students of 35 students achieve the minimum completion criteria, and in Cycle 3 there is a percentage of learning completion of 100% or overall students obtain scores above KKM. The improvement of learning outcomes from Cycle 1 to cycle 2 by 20%. Keywords: Technological Pedagogical Content Knowledge; Information Communication and Technology; PAI Learning.